Does ICT Development Flatten the Globe? Evidence from International Trade Costs Data - Keita , Moussa (American Journal of Trade and Policy, 2016)
This study attempts to bring new perspectives on the death of distance hypothesis by examining to what extent the intensification of ICT has contributed to attenuate the effect of distance on international trade issues. Our analysis is based on an extended gravity model constituted of 2827 country pairs observed from 2002 to 2012. The model is estimated by using the Hausman-Taylor instrumental variable approach to deal with specificities of the panel gravity models that cannot be treated in classical fixed-effect or random-effect models. The estimations confirm significant beneficial effects of ICT regarding trade costs reduction. We found that bilateral trade costs are significantly low between countries that have a more densified communication network. And this effect appears to be strongly heterogeneous regarding the distance. In particular, we found that the impact of ICT on trade costs is greater when the distance between the trading partners is more important. We also found that the elasticity of trade costs to distance decreases as the level of ICT increases. These results appear robust to various sensitivity and robustness checks and are consistent with other studies. Finally, the results obtained in this study suggest the existence of strong distance-neutralizing effect of ICT.JEL Classifications Code: F14 ; O33
Keywords: ICT; Distance; Trade; Trade costs; infrastructure; Gravity model